RACIAL PROBLEMS IN ZADIE SMITH'S 'ON BEAUTY' - Aqlia Nur Fahma; Imam Basuki; L. Dyah Purwita Wardani (Leksema: Jurnal Bahasa dan Sastra, 2021)
This paper discusses the problems of racism in the novel On Beauty. The analysis focuses on both individual and systemic racism represented in the novel as well as the critical position of the author. It employed Stuart Hall theory under qualitative method of analysis. The textual analysis was made to the narratives and dialogues in the novel which constitute racism in their meanings. It was concerned with how racism happens in the storyline. Meanwhile, the contextual analysis was carried out by using related references to supports the findings and the researchers’ arguments. The result showed that black women still accepted negative stereotypes and became the objects of white people’s oppressions. They were mistreated despite the application of the law on equal protection for women and minorities. In 2000s, systemic racism continued and made it even harder for black people to get the same treatment as the whites. They suffered from the policies, particularly educational policies which had led to the increase of the poverty rate of black people.